A review of more than 30 years of cytogenetic studies of Tephritidae in support of sterile insect technique and global trade. Issue 3 (12th October 2017) - Zacharopoulou, A.; Augustinos, A.A.; Drosopoulou, E.; Tsoumani, K.T.; Gariou‐Papalexiou, A.; Franz, G.; Mathiopoulos, K.D.; Bourtzis, K.; Mavragani‐Tsipidou, P.
Abstract: Cytogenetics of Tephritidae has contributed for more than 30 years to the efficient control of pest members of this family and the species delimitation among them. The sterile insect technique (SIT) is a species‐specific and environmentally friendly method for the population control of insect pest species, always as a component of integrated pest management approaches. The construction of polytene chromosome maps facilitated the development, characterization, and improvement of genetic sexing strains, which have boosted the effectiveness of SIT and are considered as models for developing genetic sexing methodologies in other target species. In parallel, characterization of mitotic karyotypes and the availability of polytene chromosomes in Diptera have been and are being used as supplementary evidence in taxonomic studies. Lately, under the common understanding that speciation can be achieved via various pathways and under the umbrella of integrative taxonomy, cytogenetic studies have contributed to multidisciplinary taxonomic approaches. Such studies can shed light on the borders between closely related species and/or incipient speciation, and this is crucial both for the implementation of SIT and the revision/improvement of quarantine policies. In this review, we summarize the cytogenetic status of Tephritidae and discuss the contribution of cytogenetics to the development of genetic sexing strains in this family.